Análise dos discursos acadêmicos sobre a voz cantada - Santana, José Reginaldo Gomes de (2013)
The discourses concerning the vocal technique, the regional traditions and the different ways of singing are inserted in an identity affirmation perspective. The very existence of these discourses in the academic environment results in conflicts between the technical discourses concerning the singing voice usage in specific subjects in the Music Degree course. In order to set the path of this study, the following specific objectives were determined: the analysis of the discourses concerning the singing voice inside the academic environment; the analysis of characteristic affirmations that may point the speaker's point of view about the established way of singing by the traditional erudite singing technique, and analyzing in the teacher's discourses characteristic affirmations that may define their point of view about the academic's opinion discourses and in the afterthought and decision making processes during the learningteaching process. Concepts and theories regarding the voice production(Travassos); imaginary formation, discursive formations and the theoretical and methodological basis of discourse analysis by the French school proposed by Michel Pêcheux notions, the identity as a movement in history and the incompletion of the discourse, subject and meaning notions, proposed by Eni Orlandi were recurred into. The empirical corpus for this research was constituted through the procedure of semi structured interviews of 6(six) academics and 2(two) teachers from the referred course. The discursive facts were analyzed through the scope of the discourse analysis by the French school. As for the discourse functioning, characteristic affirmations regarding the singing voice compared to the given as correct established way of singing by the traditional erudite singing technique and other traditions were identified; the existence of debates that generated opposite opinions in some points and agreement in other points, and discursive stances on such discourses by the academics attending the subjects regarding the production of singing voice. This research opens way to further possibilities of research in the process of construction of the musical knowledge, as well as new questionings about this subject matter in the AD.